1993
DOI: 10.1111/j.1745-4573.1993.tb00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pregelatinized Potato Starch in Low‐fat Ground Beef Patties

Abstract: Effects of modified pregelatinized potato starch (MPPS) in 5 and 20% fat ground beef patties were evaluated. In formulas containing starch, MPPS comprised 3.0% and added water 5.0% of the raw mixture. Use of 20% rather than 5% fat in the ground beef improved sensory tenderness measured early in chewing, while lowering many Instron measurements. The 20% fat patties had more intense beef flavor. MPPS increased tenderness, but reduced juiciness and beef flavor. The addition (1% of formulation) of concentrated but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 8 publications
(17 reference statements)
9
55
1
Order By: Relevance
“…The regression models indicate, and Ž . agree with other studies 13,17 , that the greater the amount of starch the lower the force required to shear Ž . the low-fat treatments.…”
Section: Lsupporting
confidence: 92%
“…The regression models indicate, and Ž . agree with other studies 13,17 , that the greater the amount of starch the lower the force required to shear Ž . the low-fat treatments.…”
Section: Lsupporting
confidence: 92%
“…In several studies, when cooking was terminated at a predetermined internal temperature or time, leaner patties have provided higher cooking yields than fatter patties (Egbert et al, 1991;Troutt et al, 1992a;Berry and Wergin, 1993). Cooking times were similar for all ground beef formulations.…”
Section: Resultsmentioning
confidence: 96%
“…However, there was no difference (p > 0.05) in hedonic scores for juiciness, tenderness and overall acceptability between the GRF and CS samples. The improvement in tenderness of the patties with the starch additives might be due to the considerable swelling of the starch granules during cooking as Berry and Wergin (1993) suggested when they indicated that the improved tenderness of patties containing potato starch was due to extensively hydrated starch granules which opened up the fibrous structure of the patties. Preference in color and beef flavor Table 2 Cook loss, moisture and fat retention and hardness of seasoned beef patties with added glutinous rice flour, corn starch, soy protein isolate and sodium tripolyphosphate.…”
Section: Sensory Characteristicsmentioning
confidence: 89%